Snakes and Labyrinths: Adhesion-Induced Fingering Instabilities in Thin Elastic Films - Davis-Purcell, Benjamin (My University, 2017)
Fingering instabilities can be observed when studying many different phenomena and display elegant pattern formation. Adhesion-induced fingering instabilities, discovered in the early 2000s, are instability patterns that arise when elastic films are sandwiched between two rigid surfaces. In this thesis we investigate this adhesion-induced fingering instability in thin elastic films. This work builds upon previous research into this instability. Experiments based on studies in the literature were performed to further examine past results; general scaling rules were confirmed, but discrepancies between current and past data show that there is still much to understand theoretically. We also perform novel experiments to elucidate the effects of strain on the instability pattern. It is found that the pattern aligns with the direction of strain in a thin film. We provide a theoretical model to explain this result.
Keywords: physics; soft condensed matter; pattern formation; instabilities; thin polymer films; adhesion